Change in household demand in the context of concerns regarding the transition to a healthy diet - Cecilia Alexandri; Bianca Pauna; Corina Saman (Amfiteatru Economic, 2025)
This article investigates household consumption in 2011 and 2021, to see if there is evidence of changes in household demands of food. The European policy from Farm to Fork aims at providing sustainable, healthy food for all consumers, through an increase in vegetable consumption at the expense of meat consumption. We estimated demand functions for 8 groups of commodities, estimating expenditure and cross-price elasticities. Our finding suggests that Romanian households still view meat as an important dietary requirement, and since its demand is one of the most elastic, the intake will further increase. The quantity and expenditure share of vegetables decreased in the interval. The expenditure elasticity shows that urban households value vegetable consumption more than rural ones. The demand for fruits is elastic, in some cases more so than the one for meat, so it is likely that the fruits demand will continue to grow. From the analysis we can conclude that Romanian households diet preferences are not fulfilling the European aim of achieving "food consumption and healthy diets", since the demand for meat continues to grow, while the demand for vegetables is at best stationary.
Keywords: D12; 330; change in the demand functions; cross-price elasticity; estimation of demand functions; expenditure elasticity